Labor markets and health: an integrated life course perspective - Benjamin C Amick; Christopher B McLeod; Ute Bültmann (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
Current work and health research is fragmented, focusing on jobs, exposures, specific worker groups, work organization, or employment contracts. An emphasis on the labor market in framing the work and health relationship conceptualizes work not only as an exposure that increases or lessens health risk but also as a life course experience that is dependent on place and time. The intention is to illustrate how the labor markets and health framework coupled with a life course perspective extends other epidemiological approaches to work and health to identify new research questions. Taking the changing nature of work and labor markets into account, this paper updates the labor markets and health framework. It then reviews, defines, and integrates key life course concepts. A model is developed that guides the understanding of how labor markets and health trajectories emerge from the consideration of the working life course in a social context. The application leads to new research questions investigating characteristics of labor markets and health trajectories that may lead to positive health outcomes over the life course.